2001
DOI: 10.1038/nm1101-1209
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic ADP-ribose production by CD38 regulates intracellular calcium release, extracellular calcium influx and chemotaxis in neutrophils and is required for bacterial clearance in vivo

Abstract: Cyclic ADP-ribose is believed to be an important calcium-mobilizing second messenger in invertebrate, mammalian and plant cells. CD38, the best-characterized mammalian ADP-ribosyl cyclase, is postulated to be an important source of cyclic ADP-ribose in vivo. Using CD38-deficient mice, we demonstrate that the loss of CD38 renders mice susceptible to bacterial infections due to an inability of CD38-deficient neutrophils to directionally migrate to the site of infection. Furthermore, we show that cyclic ADP-ribos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

22
418
3
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 419 publications
(444 citation statements)
references
References 36 publications
22
418
3
1
Order By: Relevance
“…In immunocytes, including neutrophils, CD38 produces cADPR and ADPR 50 . CD38-deficient neutrophils have disturbed Ca 2+ signaling and chemotaxis in response to fMLP via fMLP receptors 50 . Notably, the fMLP-induced Ca 2+ response and in vitro migration were suppressed in Trpm2-deficient neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…In immunocytes, including neutrophils, CD38 produces cADPR and ADPR 50 . CD38-deficient neutrophils have disturbed Ca 2+ signaling and chemotaxis in response to fMLP via fMLP receptors 50 . Notably, the fMLP-induced Ca 2+ response and in vitro migration were suppressed in Trpm2-deficient neutrophils.…”
Section: Discussionmentioning
confidence: 99%
“…All of the abovementioned functions of granulocytes are dependent on an increase of the [Ca 2ϩ ] i , although in most cases, the underlying molecular mechanisms are unknown. Involvement of cADPR in the regulation of granulocyte function was unequivocally demonstrated by Partida-Sánchez et al (7), who showed that deletion of the mammalian ADPRC CD38 renders mice susceptible to Streptococcus pneumoniae infection because of the failure of their neutrophils to migrate to the infected lung tissue. This functional impairment of the CD38 Ϫ/Ϫ neutrophils is caused by absence of the cADPR-induced [Ca 2ϩ ] i increase.…”
mentioning
confidence: 96%
“…Involvement of cADPR in the ABA-induced Ca 2ϩ increase in granulocytes prompted us to investigate the effect of ABA on the ADPRC activity, which in these cells is expressed by the transmembrane ectoenzyme CD38 (7). In intact granulocytes exposed to 20 M ABA, the ectocellular ADPRC activity increased by 70% 5 min after addition of ABA (SI Table 1).…”
mentioning
confidence: 99%
“…CD38-deficient mice show impaired humoral immune responses, neutrophil chemotaxis, and dendritic cell (DC) trafficking (21)(22)(23). Cells from CD38-deficient mice do not metabolize ecto-NAD ϩ efficiently, and the resulting higher levels of ecto-NAD ϩ lead to a higher level of ART-mediated cell surface protein ADP-ribosylation (24).…”
mentioning
confidence: 99%